Is Coal Power Generation a Sustainable Solution for Energy Needs of Pakistan: A Delphi-SWOT Paradigm? - Abbasi, Sikandar Ali; Harijan, Khanji; Memon, Zubair Ahmed; Shaikh, Faheemullah; Mirjat, Nayyar Hussain (International Journal of Energy Economics and Policy, 2020)
This paper aims to apply tools like Delphi and SWOT as a reference theme that diagnosis the sustainability of current status and future road map to develop coal based power generation in Pakistan. The SWOT analysis is performed on the themes of energy security, energy efficiency and environmental sustainability. Within this analytical framework, the coal power generation has been discussed in the context of Pakistan's energy scenario through categorical analysis of strengths, weaknesses, opportunities and threats. The paper explores the strength of coal based power production as indigenous coal reserves, internal weaknesses appears to be quality of coal (high moisture content), unavailability of water for power generation at site of coal mines and lack of coherence between coal exploitation and climate change policy. The conversion of coal to gaseous products and liquid fuels offers an opportunity alongside employing advanced technologies of High Efficiency Low Emission (HELE) to cut CO2 emissions. Threats to coal power are its adverse environmental impacts on land, soil and air. Furthermore, to enhance energy security and sustainability, strategic planning based on measures such as cleaner use of coal, promotion of renewables and energy efficiency with flexibility are suggested. Each of these actions require concrete steps from all stakeholders and policy makers to develop coherence between coal exploitation and climate change policy of Pakistan. Keywords: SWOT analysis, Delphi, Coal based power generation of Pakistan, Energy security, Environmental sustainability. JEL Classifications: P4, Q4 DOI: https://doi.org/10.32479/ijeep.10598